Increasing Medical Waste Management Literacy in Nursing and Midwifery Students at Hang Tuah University Pekanbaru: Peningkatan Literasi Pengelolaan Limbah Medis pada Mahasiswa Keperawatan dan Kebidanan Universitas Hang Tuah Pekanbaru - oktavia Dewi; Herniwanti; Emy Leonita (Universitas Hang Tuah Pekanbaru, 2026)
Medical waste is hazardous waste that may cause infections, occupational injuries, and environmental pollution if not managed appropriately. Nursing and midwifery students, as future healthcare professionals, should acquire adequate medical waste management literacy during their academic training. This community service program aimed to improve students' literacy on medical waste management through interactive health education and simulation-based training. The program was conducted on 13 October 2025 at Universitas Hang Tuah Pekanbaru and involved 10 nursing and midwifery students selected using purposive sampling. The intervention consisted of a pre-test, educational sessions, medical waste segregation simulation, group discussion, and a post-test. The results showed that the mean knowledge score increased from 32.8 before the intervention to 56.4 after the intervention, representing an improvement of 21.8 points. The greatest improvement was observed in infectious waste and sharps waste management, while knowledge related to Needlestick Injury (NSI), Personal Protective Equipment (PPE), and PostExposure Prophylaxis (PEP) required further reinforcement through repeated simulation-based training. Most participants also reported high satisfaction with both the educational content and learning methods. This program effectively improved medical waste management literacy and may serve as a simulation-based educational model for strengthening occupational safety competencies among future healthcare professionals. Abstrak Limbah medis merupakan limbah berbahaya yang berpotensi menimbulkan infeksi, cedera, dan pencemaran lingkungan apabila tidak dikelola sesuai standar. Mahasiswa keperawatan dan kebidanan sebagai calon tenaga kesehatan perlu memiliki literasi pengelolaan limbah medis sejak masa pendidikan. Kegiatan pengabdian kepada masyarakat ini bertujuan meningkatkan literasi pengelolaan limbah medis melalui penyuluhan interaktif dan pelatihan berbasis simulasi. Kegiatan dilaksanakan pada 13 Oktober 2025 di Universitas Hang Tuah Pekanbaru dengan melibatkan 10 mahasiswa keperawatan dan kebidanan yang dipilih secara purposif. Intervensi meliputi pre-test, penyampaian materi, simulasi segregasi limbah medis, diskusi, dan post-test. Hasil menunjukkan bahwa rerata skor pengetahuan meningkat dari 32,8 menjadi 56,4, atau meningkat sebesar 21,8 poin. Peningkatan tertinggi terjadi pada materi limbah infeksius dan limbah tajam, sedangkan materi mengenai Needlestick Injury (NSI), penggunaan Alat Pelindung Diri (APD), dan Post Exposure Prophylaxis (PEP) masih memerlukan penguatan melalui pelatihan lanjutan. Sebagian besar peserta juga menyatakan sangat puas terhadap materi dan metode pembelajaran yang diberikan. Kegiatan ini efektif meningkatkan literasi pengelolaan limbah medis pada calon tenaga kesehatan dan berpotensi diintegrasikan sebagai pembelajaran berbasis simulasi dalam pendidikan keperawatan dan kebidanan.